P4.51 Engaging young people from migrant and refugee backgrounds with sexual and reproductive health promotion and care in sydney, australia. (8th July 2017) - Botfield, Jessica; Newman, Christy; Anthony, ZWI
Abstract : Introduction: Migrant and refugee young people are often underserved by mainstream sexual and reproductive healthcare (SRH) in Australia and other high-income countries. Research is being undertaken to explore this, with particular emphasis on understanding the views and experiences of these young people regarding services for this aspect of health. In addition, we are exploring community, provider and policy perspectives on the complexities of engaging this diverse range of young people. Methods: A structured scoping review was undertaken to synthesise the contributions of research to understanding this topic and identify gaps in the literature. Semi-structured interviews were conducted with 23 key informants (health service providers, policymakers, academics, community advocates) to elicit their views on the complexities of, and best practice approaches to, engaging this group with SRH promotion and care. Semi-structured interviews with migrant and refugee young people are currently underway. Results: The scoping review identified two knowledge gaps: 1) perspectives of migrant and refugee young people regarding SRH health care, and 2) engagement of this group with SRH services. Key informant interviews revealed pivotal aspects of how professionals navigate this field: 1) appreciating the complexities of cultural diversity; 2) recognising structural barriers and disincentives to engagement; 3) normalising sexual health; 4) balancing 'youth-friendly' and 'culturally-competent' priorities; and 5) going beyond simple language translation to support open dialogue and meaningful engagement. Conclusion: As many high-income countries undergo demographic expansion and diversification due to migration, integrated and appropriate nation-wide frameworks for the design and delivery of SRH promotion and care is essential. The current phase of research seeks to document the views of migrant and refugee young people, aiming to capture both the synergies and divergences that are likely to be apparent between professional perspectives and the lived experience of this group of young people.